Feto-maternal correlation of PTX3, sFlt-1 and PlGF in physiological and pre-eclamptic pregnancies. (August 2014) - Algeri, Paola; Ornaghi, Sara; Bernasconi, Davide Paolo; Cappellini, Fabrizio; Signorini, Stefano; Brambilla, Paolo; Urban, Gabriele; Vergani, Patrizia
<x xml:space="preserve">Abstract</x> Objective: PTX3, sFlt-1 and PlGF levels in maternal blood are altered in some obstetric diseases, such as preeclampsia (PE). Nonetheless, only few data on their expression in the fetal compartment have been reported so far. Study Design: An observational study was performed by prospectively collecting maternal and fetal serum samples in 51 singleton pregnancies divided into two groups: 22 PE women and 29 healthy controls. The relationships between maternal and fetal marker serum levels were evaluated by Spearman correlation. Results: A feto-maternal correlation was neither identified for PTX3 in either PE or control groups (1.1 versus 3.8 ng/ml, p = 0.17 and 0.9 versus 1.3 ng/ml, p = 0.30, respectively), nor for sFlt-1 and PlGF in healthy pregnancies (158.2 versus 3326.0 pg/ml, p = 0.28 and 11.0 versus 230.9 pg/ml, p = 0.51). In contrast, PE patients showed a significant positive feto-maternal correlation for both sFlt-1 and PlGF (324.1 versus 10 825.0 pg/ml and 7.8 versus 31.6 pg/ml, respectively, p = 0.02 for both markers). Conclusion: According to our results, an independent fetal production of the analyzed soluble angiogenic markers can be hypothesized in pregnancies complicated by PE.